Morphometric responses and tolerance of pomegranate seedlings irrigated with saline water - João P. N. de Almeida; Vander Mendonça; Anderson A. Alves; Raulino Cardoso Neto; Luilson P. Costa; Francisco S. O. Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Information on the production of seedlings and initial growth of pomegranate irrigated with saline water is scarce in the Brazilian semi-arid region. The objective of this study was to assess the effect of irrigation water salinity levels on the growth and tolerance of pomegranate seedlings. The experiment was conducted in a greenhouse, located at the Federal Rural University of the Semi-Arid Region, Mossoró, RN, Brazil. A randomized block design with five treatments [electrical conductivities of irrigation water (ECw) of 0.6, 3.0, 6.0, 9.0, 12.0 dS m-1] and five replicates, with three plants per plot, was used. At 120 days after sowing, the following characteristics were evaluated: shoot, root and total lengths (cm); stem diameter (mm), dry mass of stem, leaves, root system and total (g); ratio between root and shoot dry mass; Dickson quality index and salinity tolerance. Growth and dry biomass accumulation in pomegranate seedlings were compromised with increased salinity in irrigation water, but with a lower intensity when subjected up to EC of 6.0 dS m-1. Regarding the criterion of evaluation of tolerance to salinity, pomegranate seedlings were moderately tolerant to salinity.